Quezon city trading complex - Arce, Morifredo S. Jr. (Manila : National University, 2001)
The creation of Quezon City was born from the obsession and love of the late Manuel Luis Quezon tor laboring classes of his people, Being a farsighted leader, he foresaw the population explosion in Manila, its residents. mostly workingmen in the government and private sectors spilling over the surrounding areas. Situated immediately northeast of Manila, which is the largest city among the cities and municipalities comprising Metro Manila. It would be a great advantage in promoting good trade and industry, an untapped potential of the city. Trading Complex, a structure that has physical features for the accommodation of industrial and commercial firms, small to large-scale businessman to organize trade and exhibits to promote and display their new and different kinds of products for the consumers. The complex would give a remarkable contribution for the economic development of Quezon City, bringing together business and agencies involved in intemational trade. It will provide essential trade services and will help stimulate the economy of the region it serves, and offer its members a wide range of facilities and services, which can give an access to all operating world trade centers around the globe. This project proposal will not only promote good trade and industry but will also be a good solution to the city's problem in unemployment and the sluggish growth of economic activities. Building this structure would be great prides for Quezon City for it can house-in different trade items for promotion and a good aesthetic outlook and landmark as well.
Title page -- Letter of endorsement -- Jury's approval sheet -- Acknowledgment -- Dedication -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of reference -- Chapter IV. Design framework -- Chapter V. Analysis -- Chapter VI. Conclusion/recommendation -- Bibliography -- Pictorial presentation of plates -- Appendices
Includes bibliographical references.